Assessment of Youth Participation and Institutional Support in Circular Economy Practices for Sustainable Oil Palm Development in Osun State, Nigeria (Journal of Management and Social Sciences, 2026)
Circular economy practices are increasingly promoted as sustainable responses to climate change, resource depletion, and linear production systems. In Osun State, Nigeria, the oil palm enterprise remains economically significant but faces challenges such as environmental degradation, weak institutional coordination, and limited youth involvement in sustainable innovation. This study examined youth participation in circular economy practices within oil palm enterprises and assessed the influence of institutional support in promoting sustainable development. A survey of 654 respondents across major oil palm-producing settlements in Ife, Ilesa, Irewole, and Ayedaade Local Government Areas employed descriptive statistics, cross-tabulation, correlation, and regression analyses. Findings revealed that 42.2% of youths were moderately to highly engaged in circular economy activities, while 57.8% showed minimal participation. Institutional interventions significantly enhanced involvement, with government support (β = 0.756) showing stronger predictive power than NGO assistance (β = 0.158), jointly explaining 72.2% of the variation in participation. Financial limitations, market access challenges, and knowledge gaps were major constraints. The study concludes that youth-led innovation, supported by institutional capacity and indigenous knowledge systems, is essential for achieving Sustainable Development Goals (SDGs) 8, 12, and 13. These findings imply that integrating Circular Economy training into agricultural extension services, strengthening youth-targeted funding, and promoting policy incentives for waste valorization can enhance both environmental sustainability and rural employment in Osun State. Strengthening training, and funding can unlock youth potential as key drivers of circular transformation in Nigeria’s oil palm sector.KeywordsYouth participation, circular economy, oil palm enterprises, sustainable development